Alnaa's OE Enterprise / Nurfarhana Abd Sappar... [et al.] - Abd Sappar, Nurfarhana; Nasir, Nazliah / Liah; Basirun, Aein Maftura; Setang, Sitti Ruhayah; Mohd Yusop, Erlinda (Faculty of Administrative Science & Policy Studies, 2004)
In operating our business plan and to become an entrepreneur, we should specifically and clearly state the purpose in planning our business plan. This business plan is prepared by ALNAA’s OE Enterprise (Supply and sell office equipment, stationery, and technical instrument) with the purpose areas assessing for business in form of objectively and practically, as a guideline for each partner in managing day-to-day business operation. In fact, off to avoid any wastage in managing the business resources such as wasted time to complete simple thing and wasted in using the capital buying unused tools or equipment. Also to avoid in doing a simplest mistake or carelessness that may occurred big problems to the business operation and convincing tool to attract the community which is our target customer that our business has a bright future and well planning.